The radical scavenging activity of vanillin and its impact on the healing properties of wounds - Chutima Sinsuebpol; Kanokporn Burapapadh; Verisa Chowjaroen; Narumon Changsan (Wolters Kluwer Medknow Publications, 2023)
Vanillin, an extract from the Vanilla planifolia plant, is reported to possess potent antioxidant properties. The ability of vanillin to protect skin cells from reactive oxygen species (ROS)-induced damage and its potential use in the treatment of wounds were studied. Cytocompatibility and cytoprotective properties against ROS-induced damage were examined using keratinocyte and fibroblast cell models. Vanillin's effect on cell migration was studied using the scratch wound healing assay. Vanillin exhibited cytocompatibility and cytoprotective properties against cell damage induced by ROS. Human keratinocytes and fibroblast cells showed >80% survival when exposed to vanillin (10-500 μM). Both cells showed no evidence of necrosis or apoptosis, which was confirmed by acridine orange/propidium iodide staining. Both examined cells were exposed to 750 μM hydrogen peroxide to cause oxidative stress, and vanillin demonstrated the ability to inhibit ROS-induced cell death. In addition, a considerable increase in cell migration suggested that vanillin had the ability to heal wounds in vitro. Vanillin is safe and potentially useful in wound healing treatments.